The Mis-Education of Women in Afghanistan: From Wage Premiums to Economic Losses - Rafiuddin Najam; Harry Anthony Patrinos; Raja Bentaouet Kattan (Institute of Labor Economics (IZA), 2024)
This paper uses microdata from the Labor Force and Household Surveys conducted in Afghanistan to show the wage premium differences for education between men and women, documenting a significantly larger premium for women. This sharp distinction is causal as demonstrated by analysis of the compulsory schooling law. Recent bans on women's education and employment are projected to have significant negative impacts on women's future schooling, wage growth, and national income growth.
Keywords: C13; J31; 330; returns to schooling; returns to experience; investments in education; Afghanistan